Diversified hydrogen production methods can reduce carbon dioxide emissions and energy consumption across Chinese cities - Yibo Chu; Kaile Zhou; Rong Hu; Ziwei Yang (Communications Earth & Environment)
Abstract It is still unclear about the emission reduction potential of different hydrogen production methods under different scenarios in China. Therefore, this study quantifies and predicts the life cycle emission reduction potential of hydrogen energy across Chinese cities. Here we quantify the life cycle carbon dioxide emissions of different hydrogen production methods in 5 selected pilot cities. Additionally, we evaluate the respective contributions of blue hydrogen and green hydrogen to emission reductions under different scenarios. The results show that the implementation of diversified hydrogen production methods results in reductions in carbon dioxide emissions, ranging from 65% to 96%, when compared to the utilization of single coal gasification for hydrogen generation by the year 2060. Blue hydrogen has the potential to achieve a emission reduction of 3.4 million tons by 2055. By 2050, green hydrogen is projected to constitute over 50% of the hydrogen supply market.